2014
DOI: 10.1371/journal.pone.0105192
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Serum MicroRNAs Panel as Potential Biomarkers for Diagnosis of Nonalcoholic Fatty Liver Disease

Abstract: BackgroundThe invasive nature of liver biopsy makes the histopathological diagnosis of non-alcoholic fatty liver disease (NAFLD) difficult and its diagnostic performance unsatisfactory. The present study aimed to identify a serum microRNA (miRNA) expression profile that could serve as a novel diagnostic biomarker for NAFLD.MethodsSerum miRNA expression was investigated using three cohorts comprising 465 participants (healthy controls and NAFLD patients) recruited between August 2010 and June 2013. miRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 40 publications
(53 reference statements)
4
148
1
Order By: Relevance
“…We detected a correlation between serum and hepatic miR122 expression, in agreement with other authors [45], which suggests that miR122 released from hepatic cells enters the bloodstream. However, Pirola et al described an inverse relationship between the circulating and tissue expression of miR122 , and suggested that the lower expression of miR122 in liver is a consequence of a high rate of release into the circulation [26].…”
Section: Discussionsupporting
confidence: 92%
“…We detected a correlation between serum and hepatic miR122 expression, in agreement with other authors [45], which suggests that miR122 released from hepatic cells enters the bloodstream. However, Pirola et al described an inverse relationship between the circulating and tissue expression of miR122 , and suggested that the lower expression of miR122 in liver is a consequence of a high rate of release into the circulation [26].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, only the elevations in miR-34a and miR-122 were significant in both men and women. Tan et al identified miR-122–5p, miR-1290, miR-27b-3p and miR-192–5p as a panel of high diagnostic accuracy for NAFLD in a population with low BMI (25.2 kg/m 2 ) and low NAS scores [52]. Similarly, Celikbilek et al .…”
Section: Discussionmentioning
confidence: 99%
“…In similar fashion, miR-122, the most abundant miRNA of the liver, was also found at high level in sera from HCC patients [71,72] . However, the level of circulating miR-122 may be strongly influenced by inflammation or apoptosis of hepatocytes in such conditions as acute or chronic hepatitis or nonalcoholic fatty liver disease, suggesting that background condition of the liver inflammation may strongly influence the miR-122 level [74] . Nevertheless, the data from candidate-based studies correlate with the data from Link et al [54] at least for both miRNAs miR-21 and miR-122 [69] .…”
Section: Mirnas As Non-invasive Diagnostic Biomarkers For Hccmentioning
confidence: 99%